6xy-2x+3cy-c=

Simple and best practice solution for 6xy-2x+3cy-c= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6xy-2x+3cy-c= equation:


Simplifying
6xy + -2x + 3cy + -1c = 0

Reorder the terms:
-1c + 3cy + -2x + 6xy = 0

Solving
-1c + 3cy + -2x + 6xy = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '2x' to each side of the equation.
-1c + 3cy + -2x + 2x + 6xy = 0 + 2x

Combine like terms: -2x + 2x = 0
-1c + 3cy + 0 + 6xy = 0 + 2x
-1c + 3cy + 6xy = 0 + 2x
Remove the zero:
-1c + 3cy + 6xy = 2x

Add '-6xy' to each side of the equation.
-1c + 3cy + 6xy + -6xy = 2x + -6xy

Combine like terms: 6xy + -6xy = 0
-1c + 3cy + 0 = 2x + -6xy
-1c + 3cy = 2x + -6xy

Reorder the terms:
-1c + 3cy + -2x + 6xy = 2x + -2x + -6xy + 6xy

Combine like terms: 2x + -2x = 0
-1c + 3cy + -2x + 6xy = 0 + -6xy + 6xy
-1c + 3cy + -2x + 6xy = -6xy + 6xy

Combine like terms: -6xy + 6xy = 0
-1c + 3cy + -2x + 6xy = 0

The solution to this equation could not be determined.

See similar equations:

| 8x-6=x+4 | | U^4w^4-u^4=0 | | 12x+(9x-3)-(10x-2)=12 | | 11/4-21/16 | | Y=11-6x/4 | | 5h+6(8h-1)= | | 4/9=2u | | 25d+50=175 | | 15x+5=14x+11 | | a=1/2bh;b=10,h=8 | | x+(x+1)=122-3(x+2) | | n/30-2=3 | | 7=12-5x+4y | | 7f-3=39 | | x-3/5=-1 | | 46-2=8 | | 3x^4-14x^2-24=0 | | 50e-1=799 | | y-(-5)=9x+18 | | a/8-2=8 | | 2-x/2=8-x/3 | | 4(g+8)+7+4g= | | 11k-5=61 | | 8y=2x-48 | | 15y+10=85 | | u^3=27 | | 2-x+9=3x+8 | | (x-45)+(x-45)+(x-45)+2x=540 | | 3n+12=52 | | -3y=2x+12 | | 3(1.2b-1)+36=4.2 | | f(1)=1.5n+6 |

Equations solver categories